2019
DOI: 10.5539/ijef.v11n11p43
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture and Non-Agriculture Growth, Inflation and Income Inequality in Developed and Developing Countries

Abstract: The aim of this article is to examine how agriculture and non-agriculture growth and inflation affect income inequality. The multivariate panel data approach is used to examine the application of Kuznets hypothesis between income inequality and agriculture and non-agriculture growth and test the existence of nonlinear relationship between income inequality and inflation rate in a large sample of data collected for developed and developing countries. The Hodrick-Prescott (HP) filter is used to separate the cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In all models, the coefficients of the CPI inflation are positively significant. It means that a rise in the CPI inflation, as an indirect effect of monetary policy shocks, can increase income inequality, which is consistent with the results of previous studies (Shiller, 1996; Easterly & Fischer, 2001; Amornthum, 2004; Siami‐Namini, 2019; Siami‐Namini & Hudson, 2019a,b). No matter what measures are used as an income inequality indicator in the estimated models, the effects of CPI inflation on income inequality are similar for all individual measures.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In all models, the coefficients of the CPI inflation are positively significant. It means that a rise in the CPI inflation, as an indirect effect of monetary policy shocks, can increase income inequality, which is consistent with the results of previous studies (Shiller, 1996; Easterly & Fischer, 2001; Amornthum, 2004; Siami‐Namini, 2019; Siami‐Namini & Hudson, 2019a,b). No matter what measures are used as an income inequality indicator in the estimated models, the effects of CPI inflation on income inequality are similar for all individual measures.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, sectors’ growth and inflation affect income inequality in the long run. By using panel time series analysis, Siami‐Namini (2019) analysed the existence of Kuznets hypothesis between agriculture and non‐agriculture growth and income inequality and examined the existence of the non‐linear relationship between inflation and income inequality in both developed and developing countries. The results confirmed the existence of a “U‐shaped” of Kuznets curve between agriculture growth and income inequality on one hand and between non‐agriculture growth and income inequality on the other hand in developed countries.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Dinçer and Yuksel (2019) in a study on E7 countries revealed a long-run relationship between total expenditure and public health expenditure and no causal relationship. Siami-Namini (2018) also made a related study for a period from 1995 to 2013 in G7 countries. The findings showed existence of short-run unidirectional linkages from per capita GDP to per capita health expenditure.…”
Section: Literature Reviewmentioning
confidence: 99%